VARIASI PUSH UP DAN HAND GRIP UNTUK PASSING ATAS BOLA VOLI PUTRI CLUB ORYZA - Ahmad Jaza Riadi; Jhony Hendra; Desi Tri Susanti (Master of Physical Culture and Recreation in Nusantara, 2025)
This study was motivated by the low overhand passing skills of the women’s volleyball players of Club Oryza. This was indicated by the inconsistency of ball accuracy and the lack of arm muscle strength in controlling ball direction. Therefore, a more targeted physical training program is needed to improve the basic ability of overhand passing. The purpose of this research was to determine the effect of push-up and hand grip exercises on improving the overhand passing skills of the women’s volleyball players of Club Oryza. The research method used was a quasi-experimental design with a one-group pretest-posttest model. The population consisted of 40 players, while the sample comprised 20 players selected using purposive sampling. The research instrument was an overhand passing skill test, and the data were analyzed using the Shapiro-Wilk normality test and the Paired Samples T-Test with the assistance of SPSS version 23. The results showed an increase in the average score from the pretest value of 34.1 to the posttest value of 45.8. The Paired Samples T-Test produced a t-count of -12.283 with a significance value of 0.000 < 0.05. When compared to the t-table value at a 5% significance level (df = 19) of 1.7291, the t-count was greater than the t-table. Thus, push-up and hand grip training had a significant and effective influence on improving the overhand passing skills of the women’s volleyball players of Club Oryza.